Observational learning and willingness to pay in equity crowdfunding - Martin Walther; Marco Bade (Business Research, 2020)
This study examines interdependencies between investments of equity crowdfunders. Based on hand-collected data from a well-established equitycrowdfunding platform, we find strong indication that investors observe previous investments to determine their willingness to pay for equity shares. Furthermore, the investment behavior of predecessors may lead investors to deviate from average investment behavior. In particular, investors are willing to pay more than the average investment, when the focal campaign is hot or there have been many large investments in the campaign. Remarkably, a high number of all previous investments over the entire period of the campaign as well as co-financing by presumably sophisticated investors negatively influence willingness to pay. This suggests that crowd investors are subject to partial crowding-out. These findings are different on the platform level, which suggests that investors' behavior is rather information than sentiment-driven.
Keywords: 650; Equity crowdfunding; Observational learning; Crowding out; Investment interdependencies; Individual investment behavior